ANALISIS PENGGUNAAN MEDIA VIDEO PEMBELAJARAN ETNOMATEMATIKA TARI JEJER GANDRUNG KEMBANG MENUR SEBAGAI HASIL BELAJAR SISWA - Sofia Novaliyanti Mahmuda; Susanto Susanto; Erfan Yudianto (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2019)
Abstract: Mathematics has an important role in education and other sciences. Generally learning mathematics seems conventional and theoretical, so students assume that mathematics seems stiff, difficult, and boring. Education can be combined with local culture in creating a more contextual education atmosphere, especially in the mathematical concept commonly referred to as ethnomatematics. This study aims to examine the use of video media for learning ethnomatematics Traditional Dance of Gandrung Kembang Menur typical of Banyuwangi on increasing student interest in learning. This study uses qualitative methods, the data obtained is the result of pre-test and post-test with 8 multiple choice questions. The results showed that there was an utilization of Etnomatematics learning video media on the Jejer Gandrung Kembang Menur dance typical of Banyuwangi in the process of influencing student learning outcomes. Keyword: Video learning, learning outcomes, ethnomatematics, gandrung jejer dance development, gandrung jejer dance.